Terapi Sayyidul Istighfar Guna Mengurangi Kecemasan Akademik - Fawaid, Muhammad Badrul; Fahmi, Lukman; Nuha, Moch. Syihabudin (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
One of the psychological problems often experienced by students is academic anxiety. Academic anxiety refers to feelings of worry about threats coming from the academic environment, such as lecturers, subjects, or certain courses. Symptoms that often appear in students include difficulty concentrating, trembling, and a faster heartbeat. Sayyidul Istighfar is a servant's request to Allah to cover his sins, avoid torture, and ask for forgiveness. Linguistically, istighfar includes two requests: covering sins and forgiveness. This study aims to determine the effect of Sayyidul Istighfar in reducing academic anxiety. The method used in this study is library research, namely research that collects various information from library sources such as books and scientific journals. The results of this study indicate that Sayyidul Istighfar therapy is effective in reducing academic anxiety in students, so that it can be a new form of intervention that can be used as a reference in curative and preventive efforts against academic anxiety in students.